Revitalizing Madihin in the Digital Era: Cultural Education Strategies Amidst Globalization in South Kalimantan - Muhammad Budi Zakia Sani; Wadiyo Wadiyo; Syakir Syakir; Suminto A Sayuti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Madihin is a traditional Banjar oral art form that conveys moral, religious, and cultural values through poetry and humor. However, globalization and digitalization have challenged its continuity, especially among younger generations. This study investigates how Madihin is being revitalized through digital platforms and its function as a medium for cultural and character education in South Kalimantan. Using a qualitative approach with a digital ethnography framework, the study collected data through in-depth interviews, participant observations, and analysis of online Madihin content on YouTube, TikTok, and Instagram. Participants included Madihin practitioners, educators, students, and cultural stakeholders. Findings reveal that digital media has expanded the reach of Madihin, increased youth engagement, and fostered creative innovations. Madihin supports character education by embedding values such as honesty, respect, and social responsibility into engaging performances. It also promotes digital literacy by encouraging ethical media use and critical thinking. However, challenges such as content commodification, authenticity loss, and digital inequality persist. Madihin’s revitalization in the digital era highlights the adaptive potential of traditional arts in contemporary education. To ensure sustainability, collaboration among schools, communities, and government bodies is essential. When aligned with educational goals and cultural identity, Madihin can function as both an instructional tool and a medium for cultural preservation.